MORPHOLOGY, GENETICS, AND BIOCHEMICAL COMPOUNDS CHARACTERIZATION OF TWO TROPICAL MARINE MICROALGAE ISOLATES - HANDAYANI (NIM: 20515006), YUNI
Microalgae is a unicellular photosynthetic water plant, which can produce many promising biochemical compounds. Biodiversity of microalgae in Indonesian ocean is very high but so far just a few of them have been already identified taxonomically. Microalgae identification could be done morphologycally and genetically. This research aims to identify morphologycally and genetically two strains (MA1 and MA2) of tropical marine microalgae isolated from Muara Angke, Indonesia, and to characterize their biochemical compounds. This research conducted in several steps including: (i) purification of microalgae samples, (ii) cultivation of pure microalgae and construction of the growth curves, (iii) analysis of the morphology using light microscope and SEM, (iv) analysis of the genetics based on 18S rDNA V4, LSU D2/D3, and rbcL-3P genes, and (v) determination of total lipid and protein from the biomassa of the microalgae. Both of the microalgae (MA1 and MA2) could grow well in f/2 medium and they reached the stationary phase at the seventh day. They have same morphologies, i.e. a golden brown color and spherical cell shape. They make a colony which is several cells connected together in a long chain by IFPP (Intercalary Furtoportula Process). These morphologies are similar to the Skeletonema genus, so the strains are named as Skeletonema MA1 (SMA1) and Skeletonema MA2 (SMA2). IFPP of MA1 is knuckle-like and of MA2 is knot-like. SMA1 and SMA2 have successfully been analyzed by 18S rDNA V4 and LSU D2/D3 genes. In addition, SMA2 has been analyzed with rbcL-3P gene. Results showed that, based on gene fragment of 18S rDNA V4 SMA1 and SMA2 are closest to S. cf. pseudocostatum. Based on LSU D2/D3 gene fragment, SMA1 and SMA2 are closest to S. tropicum. Based on rbcL-3P gene fragment, SMA2 is closest to S. grethae. The dried biomass productivity of SMA1 and SMA2 are 46,23+-3,24 mg L-1d-1 and 47,38+-0,29 mg L-1d-1, respectively. The total lipid content in the biomass for SMA1 and SMA2 are 42,42%+-4,35 and 20,43%+-0,68 (weight of lipid in the weight of dried biomass), respectively, whereas for total protein content for SMA1 and SMA2 are 31,39%+-0,38 and 29,82%+-5,4 (%protein in weight of dried biomass), respectively. Palmitoleic acid is the most abundant fatty acid, i.e. 22,16% in total fatty acid of SMA1 and 22,86% of SMA2.